2020
DOI: 10.3389/fnhum.2020.00101
|View full text |Cite
|
Sign up to set email alerts
|

Action Real-Time Strategy Gaming Experience Related to Increased Attentional Resources: An Attentional Blink Study

Abstract: Action real-time strategy gaming (ARSG) is a cognitively demanding task which requires attention, sensorimotor skills, team cooperation, and strategy-making abilities. A recent study found that ARSG experts had superior visual selective attention (VSA) for detecting the location of a moving object that could appear in one of 24 different peripheral locations (Qiu et al., 2018), suggesting that ARSG experience is related to improvements in the spatial component of VSA. However, the influence of ARSG experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 95 publications
(164 reference statements)
2
38
0
1
Order By: Relevance
“…This study used the recruitment procedure established in previous research (Qiu et al, 2018 ; Gong et al, 2019b ; Gan et al, 2020 ). All the participants in the current study were college students of the University of Electronic Science and Technology of China (UESTC) who responded to the recruitment flyers posted on campus or on the Internet forums hosted by the UESTC.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This study used the recruitment procedure established in previous research (Qiu et al, 2018 ; Gong et al, 2019b ; Gan et al, 2020 ). All the participants in the current study were college students of the University of Electronic Science and Technology of China (UESTC) who responded to the recruitment flyers posted on campus or on the Internet forums hosted by the UESTC.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the results, eight additional individuals were excluded prior to the experiment because they had moderate/severe depression or anxiety (i.e., SDS ≥ 63 or SAS ≥ 60; n = 5) and Internet gaming disorders ( n = 3). The participants also reported their: (1) gaming experience in the recent 2 years and expertise gaming ranking of League of Legends (LOL)—the ARSG game used in this study; (2) LOL ID, which was used to validate the participants’ self-reported gaming experience and expertise; and (3) gaming experience of other gaming genres in the recent 2 years to ensure that LOL was the major game genre for all the participants (Qiu et al, 2018 ; Gong et al, 2019b ; Gan et al, 2020 ). All the participants were right-handed and had normal or corrected-to-normal vision and no history of mental and neurological diseases.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations